Analysis of the Influence of Family Support and Medical Personnel, Medical Personnel Competence on Childbirth Planning Decisions with Patient Experience at the Obstetrics Polyclinic as an Intervening Variable at Mayapada Hospital Kuningan - Denny Khusen; Natsir Nugroho; Idrus Jus'at; Rokiah Kusumapradja (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
The background of this research is relevant to evaluate and improve services in Mayapada Hospital Kuningan , especially in the obstetrics polyclinic. By understanding the relationship between family support and medical personnel, medical personnel competence, patient experience to the obstetrics polyclinic as an intervening variable, and the decision of the birth plan. In addition, there is also a need to evaluate the factors that influence the decision of the birth plan. The purpose of the study is to analyze influence family support and medical personnel, the competence of medical personnel simultaneously with patient experience at the obstetrics polyclinic regarding the decision to plan childbirth at Mayapada Hospital Kuningan. Method Study, this is study associative causality with cross sectional design. This study aims to determine the influence of family support and medical personnel (X1), the competence of medical personnel (X2) on the decision of birth plan (Y) with the patient's experience to the obstetric polyclinic as an intervening variable (Z). The findings of this study are from the statistical test analysis we can find that the most influential variables on the decision of birth plan are family support and medical personnel. The results of the study say that the patient's experience to the polyclinic as an intervening variable does not affect the decision of birth plan. The implications of this study can help management in improving the system for family support and medical personnel, the competence of medical personnel and the patient's experience to the obstetric polyclinic so that it is expected to improve the decision of birth plan to the hospital.